Pengembangan E-Modul Berbasis Socio-Scientific Issue (SSI) Terintegrasi HOTS pada Materi Kesetimbangan Kimia - Ambarita, Putri Theresia; Dalimunthe, Makharany (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The low learning outcomes of students in chemistry subjects are caused by teachers still not implementing the existing learning model, the teaching materials used are still sourced from schools and there are no interactive teaching modules that are considered quite practical in learning activities. The questions used during the evaluation are still dominant in the LOTS type in the 21st century learning era which emphasizes learning with a Higher Level Thinking style (HOTS). To address this problem, this study aims to develop a valid HOTS-integrated socio-scientific issue (SSI) based e-module on chemical equilibrium material. This research uses the Research and Development (R&D) method with a 4D development model from Thiagaranjan which is limited to the 3D stage, namely Define, Design, and Develop. The subjects in this study are 3 lecturers and 2 teachers as validators of material and media experts. The object of this research is an SSI-HOTS-based e-module on chemical equilibrium material. The instruments used, namely non-test instruments, include student needs analysis questionnaires, interview sheets and material and media expert validation questionnaires. The results of the validation of SSI-HOTS-based e-modules on chemical equilibrium materials were declared very valid, with the average percentage of the score of the assessment results of the material expert validator of 91.67% and the average percentage of the score of the assessment results of the media expert validator of 90%. Thus, this e-module has the potential to be an innovative teaching material alternative that is practical and supports the improvement of students' understanding of the concept of chemical equilibrium and higher-level thinking skills.